Organizational Culture and Innovative Work Behavior: The Roles of Job Satisfaction and Innovation Challenge Stressors - Nguyen, Hoa Dinh; Vu, Thanh Ba (Organizations and Markets in Emerging Economies, 2026)
This study investigates the mechanisms through which clan culture and adhocracy culture influence employees’ innovative work behavior via the mediating role of job satisfaction and the moderating role of innovation challenge stressors in manufacturing and service firms in Ho Chi Minh City. A quantitative research design was employed, and a structural equation model (SEM) was tested using Amos with a sample of 283 employees working in manufacturing and service firms. The results indicate that both clan culture and adhocracy culture have positive effects on job satisfaction and both directly and indirectly enhance innovative work behavior through job satisfaction. Job satisfaction plays a significant mediating role in the relationships between clan culture, adhocracy culture and innovative work behavior. In addition, innovation challenge stressors appraised as challenges positively moderate the relationship between job satisfaction and innovative work behavior, suggesting that when employees are satisfied with their jobs and simultaneously experience higher levels of innovation challenge stressors, they are more likely to actively engage in behaviors that generate, champion, and implement new ideas.